969 Intra-Abdominal Rectal Perforation Post Haemorrhoidal Artery Ligation Operation (HALO) And Converted Ligasure Open Haemorrhoidectomy. (12th October 2021) - Simon, N; Saiyara, N; Gercek, Y
Abstract: Case Report: Symptomatic prolapsing haemorrhoids are usually treated with either haemorrhoidal artery ligation operation (HALO), stapled haemorrhoidopexy or open haemorrhoidectomy. Complications are rare with serious complications like rectal perforation reported scarcely in literature. We report a case of intraperitoneal rectal perforation following transanal haemorrhoidal artery ligation and converted open Ligasure-assisted haemorrhoidectomy in a 74-year-old lady with background portal hypertension secondary to primary biliary cirrhosis. We present this case to highlight the importance of preoperative medical optimisation of portal hypertension prior to surgical intervention and consideration of primary open techniques in grade 4 haemorrhoid surgery.